Produções de sentidos em um arquivo pessoal: As ilustrações de figurinos de Alceu Penna para o show Brazil Export (1972) - Penna, Gabriela Ordones (2016)
Alceu Penna (1915-1980), creator of the column's Girls of Alceu in The Cruzeiro magazine, became a reference in fashion and behavior by their graphics in the mid-twentieth century. Alongside this activity in the press, he developed a solid and little-known career designing costumes for various shows between the 1930s and 1970s, including the show mulatto-export type Export Brazil (1972) of Abelardo Figueiredo. Thinking illustration as a historical document, that is, as a visual image from which (and where) produces senses, the thesis is concerned with analyzing the Alceu Penna costumes graphics for this show, located in his personal archive, as visual and material evidence in which are impregnated traces of its making and circulation, in addition to visual dialogues established with its surroundings. Every detail contained in the illustration, as his paper, the technique used, the materials used, the author's signature, the wear of time, the colors, all this is treated as important indicators for an interpretation of the work's meaning production.